การพัฒนารูปแบบการจัดกระบวนการเรียนรู้ตามแนวคิดโฟร์แม็ทซีสเต็มเพื่อส่งเสริมทักษะการสอนของครูประจำกลุ่มการศึกษานอกโรงเรียน - วิเชียร หรูวิจิตร์พงษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The purposes of the research were (1) to study the state and problems of instruction of the facilitators (2) to develop a learning process model based on The 4 MAT System approach. (3) to study the factors involving with an applied learning process model based on the 4 MAT System approach. The target groups were the facilitators in Non-Formal Education Centers 2 and the Centers 4. The research could be divided : Phase I : Studying the learning problems of the facilitators., Phase II : Developing a learning process model based on the 4 MAT System approach and training the facilitators. By using The target group was the facilitators in Non-Formal Education Centers 2 and Centers 4 which were divided into 2 groups : a control group and an experimented group which had been trained of a learning process model based on The 4 MAT System approach for 2 days (6 hours a day). Phase III : Studying the factors which affected with using this model. The results were : 1. the state and problems instruction of the facilitators were teachers, students, and teaching techniques, 2. a learning process model based on The 4 MAT System approach consisted of (1) basic belief patterns (2) model objective (3) process and (4) results 3. The results of trying this model were the post-test learning scores of the experiment group higher than that of the control group significantly at the .05 level and the factors affected this model were teachers, students and the learning activities.